U UJI AKTIVITAS ANTIBAKTERI SEDIAAN GEL HAND SANITIZER SANITIZER BUNGA LAWANG (Illiacium verum Hook. f) pada BAKTERI Staphylococcus aureus & Escherichia coli - Novarianti Marbun (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2023)
Some diseases caused by microorganisms on the hands are diarrhea, diphteria, boils, typhus and others. The bacteria that most often contaminate the skin of the hands are Staphylococcus aureus and Escheria coli, whose spreas most often transmitted from hand to hand. Bunga lawing are one of the medicinal plants that have been used in medicine. The purpose of this study was determine the antibacterial activity of gel hand essential oil sanitizer gel preparation (Illiacium verum Hook.f) to the growth of Staphylococcus aureus and Escheria coli bacteria compared to sanitizer Dettol gel hand. This was carried out with the experimental method. Essential oil of bunga lawing is extracted using a heat method, namely soxhletation. The antibacterial activity test in this study used the agar diffusion method (disc diffusion). The measurement of the diameter of the inhibited area formed were analyzed using a one-way ANOVA statistical test. The results of antibacterial activity of bunga lawang sanitizer hand have lower antibacterial activity gel hand sanitizer Dettol. In the diameter of Staphylococcus aureus bacteria the highest rate 0f hand flower sanitizer gel was 15,1 mm while the sanitizer gel hand wash 21,4 mm. In Escheria coli bacteria, the inhibitory diameter the sanitizer hand gel dettol was obtained at 20.1 mm, while the lawang hand sanitizer gel obtained the highest inhibition diameter of 13.1 mm. The results of data analysis using a one-way ANOVA statistical test showed a sig value p<0,05 so that there were significant differences between the gel hand to the inhibitory power of the growth of Staphylococcus aureus and Escheria coli bacteria.